Effect of yoga asana and pranayamaonP300- an event related potential in type2 diabetes - Jangid, Naina; Prabha, Raj; Dhakar, Prahlad; Zenab, Ambreen; Bishnoi, Preeti (Journal of Bangladesh Society of Physiologist, 2025)
Background: The P300 (Event related potential) occurs almost 300msec subsequent to the given stimulus, a precise measure of neuronal functioning. The shorter latencies are associated with superior cognitive performance. In diabetes mellitus hyperglycemia has the strongest association in developing the risk of cognitive impairment and prolonged P300 latencies. Objective: To observe the effect of yogasana and pranayama on P300 latencies and amplitudes in diabetic patients. Method: An interventional study was done in Physiology Department, Rajastana University Health Science(RUHS) college of medical science(CMS), Jaipur, India. Total 120 patients with type 2 diabetes of both sexes aged 40 to 60 years d 60 were recruited by simple random sampling and randomized equally into two groups. study group included 60 patients assigned with yoga intervention for 45 days and control group included 60 patients without yoga. An event related potential P 300 was measured by NCV/EMG machine, Clarity India After collecting baseline data of all diabetic patients, yoga intervention was given for 45days in study group subjects only. Post yoga data was collected in study group and post 45 days data in control group. Data was statistically analyzed using student paired and unpaired t test. Result: Mean P300 latency in study group significantly decreased from baseline after yoga (at Cz-A1322.14±18.95 to 312.96±13.31msec p-value 0.002 and at Cz-A2 331.64±19.60 to 319.17±11.75 msec p-Value0.0001). Mean P300 amplitude significantly decreased in control group after 45 days. (atCz- A216.49±5.09μV to 14.77±4.30μVpValue 0.047). Conclusion: This study concluded that yoga can effectively reduce event related potential P300 latencies and enhance amplitude in type 2 diabetes mellitus patients. J Bangladesh Soc Physiol 2024;19(2): 55-60